Cloud Resolving WRF Simulations of Precipitation and Soil Moisture Over the Central Tibetan Plateau: An Assessment of Various Physics Options. Issue 2 (27th January 2020) - Lv, Meizhao; Xu, Zhongfeng; Yang, Zong‐Liang
Abstract: The evaluation of the regional climate model is of great importance for model's developments and applications. We assessed the performance of Weather Research and Forecasting (WRF) cloud resolving simulations with various physics options in terms of precipitation and soil moisture over the central Tibetan Plateau (TP) for a 2‐month simulation from July to August in 2015. The simulated precipitation is most sensitive to the microphysics scheme, followed by the land surface model, which plays a vital role in the soil moisture simulation, while the planetary boundary layer and radiation schemes have relatively minor impacts on the precipitation and soil moisture. Specifically, the heavy precipitation event has a close relationship with the land surface model. Among the different WRF schemes, the new Thompson microphysics scheme, the Noah land surface model, the GFDL radiation scheme, and the Mellor–Yamada planetary boundary layer scheme perform relatively better than other options over the central TP. In contrast, the Lin and WRF Single‐Moment 6‐class microphysics schemes tend to simulate an earlier precipitation peak in the diurnal cycle, excessively higher intensities, and greater frequencies for high precipitation events. The Rapid Update Cycle model performs the worst in the spatiotemporal pattern of precipitation and markedly exaggerates the diurnal variation of soil moisture. These results can provide valuable guidance for further fine‐scale simulation studies of land–atmosphere interaction over the TP. Key Points: The optimization of the physics schemes over the Tibetan Plateau (TP) is directly relevant to the land‐atmosphere coupling study A comprehensive evaluation for the effect of various physics schemes on the precipitation and soil moisture in the central TP is conducted